EPIDEMIOLOGY AND RISK FACTORS OF CHRONIC KIDNEY DISEASE IN YOUNG ADULTS: A NARRATIVE REVIEW IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To summarize and update global data on the prevalence and risk factors of CKD in young adults up to 2025.Subject and method: This narrative review included international studies published between 2015 and 2025 retrieved from PubMed, Google Scholar, and Web of Science, focusing on individuals aged 18–39 years.Results: The prevalence of CKD among young adults ranged from 3% to 6%, lower than in the general population (9–10%), and most cases were at early stages (stages 1–2). The burden was higher in Asia and Latin America. Major risk factors included metabolic disorders-particularly hypertension, diabetes mellitus, and obesity-followed by glomerular diseases, genetic predisposition, chronic infections, and environmental or toxic exposures. Early-life factors such as prematurity and low birth weight also contributed to increased susceptibility to CKD.Conclusion: The prevalence of chronic kidney disease among young adults aged 18 to 39 years is approximately 3%–6%, with most cases occurring in the early stages (stages 1–2). The principal risk factors include metabolic disorders, particularly hypertension, diabetes mellitus, and obesity. Other important contributors include glomerular diseases, genetic factors, chronic infections, and environmental or toxic exposures.
Keywords: chronic kidney disease, young adults, epidemiology, risk factors.